Vegetarian for Maternal and Child Health - Sumiasih, Ni Nyoman (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Maternal and child health is the first priority to be addressed as it is the source of future generations and indicators of progress of a nation. To maintain the health of mothers and children, one important factor is nutrition, one of which is a vegetarian who is often doubted by many people and considered unable to guarantee health. This paper aims to provide information about how vegetarianism is a valuable and supported nutrient if it can be arranged and properly arranged. The method in this research is literature study. All the nutrients obtained from animal sources can also be obtained from vegetable sources, as we know that animals eat plants. Thus, the elements contained in the animal body are the elements present in plants. So, food from vegetable is actually almost the same, as long as it can be arranged well in the menu. Nowadays vegetarians have been scientifically proven in developed countries, so the development of vegetarians is very advanced. Some nutrients such as essential amino acids, vitamin B12, iron (Fe) and other nutrients such as carbohydrates, fats, vitamins, minerals and fiber are not problematic in pregnant women and vegetarian children, because these needs can be met from vegetable. Vegetarian is a nutrient derived from the meatless vegetation that is the result of the murder. But to complement the need for essential proteins need to be supplemented with milk or dairy products like cheese, yogurt and others.